2002
DOI: 10.1034/j.1399-0004.2002.610509.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial lethal skeletal dysplasia with cloverleaf skull and multiple anomalies of brain, eye, face and heart: a new autosomal recessive multiple congenital anomalies syndrome

Abstract: We report on a 'new' lethal familial short-limb bone dysplasia associated with multiple anomalies in three sibs born to Arabic-Muslim consanguineous healthy parents. Clinical abnormalities included short limbs and short hands, cloverleaf skull, frontal bossing, wide anterior fontanel, hypertelorism, bilateral microphthalmia, cataract, low-set ears, narrow chest, ambiguous genitalia, cardiac ventricular septal defect (VSD) and agenesis of the corpus callosum. Radiological abnormalities included cloverleaf skull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The opacity in congenital cataracts ranges from a small dot to total clouding of the lens. Approximately one‐third of cases are idiopathic, and many of these are familial or hereditary; both autosomal dominant and autosomal recessive modes of inheritance have been reported17, 29, 30. The remainder are probably caused by intrauterine infection (rubella, toxoplasmosis, cytomegalic inclusion disease and syphilis), chromosomal disorders (trisomies 13, 18, 20 and 21 and Turner's syndrome), or systemic disorders12, 15, 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opacity in congenital cataracts ranges from a small dot to total clouding of the lens. Approximately one‐third of cases are idiopathic, and many of these are familial or hereditary; both autosomal dominant and autosomal recessive modes of inheritance have been reported17, 29, 30. The remainder are probably caused by intrauterine infection (rubella, toxoplasmosis, cytomegalic inclusion disease and syphilis), chromosomal disorders (trisomies 13, 18, 20 and 21 and Turner's syndrome), or systemic disorders12, 15, 31.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature7–25, 30 it became obvious that a history of fetal eye anomalies leads to a diagnosis in the first half of the pregnancy. However, the absence of risk factors should not preclude the possibility of this occurrence, although we observed that in families with no family history of fetal eye anomalies, the diagnosis was made only late in the third trimester, usually during second‐opinion sonography.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of heart defects with skeletal dysplasias has been amply reported both in human classical recognizable syndromes [Kozlowsky et al, 1974; Spranger and Maroteaux, 1990] and in new syndromes [Sharony et al, 2002]. Mutations of single genes involved both in skeletal and heart development begin, on the other hand, to be discovered.…”
Section: To the Editormentioning
confidence: 99%
“…The ineffectiveness of the current available laws or edicts on TOP is readily evident from the distressing outcomes endured by the Muslim populations of the world due to foetal anomalies [2-29], including even those residing in developed nations [2,4,5,10,16,20,21,23-29]. …”
Section: Introductionmentioning
confidence: 99%